Socio-economic determinants of suicide in Singapore : a time series analysis with the autoregressive distributed lag (ARDL) approach to cointegration - Liew, Kam Yew (2014)
Suicide is one of the major causes of death in Singapore even the yearly suicide rates are relatively low as compared to other developed countries. This project examines the determinants of suicide in Singapore for the period of 1980-2012. We estimate the dynamic econometric models for aggregate, male and female suicides by using the Autoregressive Distributed Lag (ARDL) approach to cointegration. Our empirical results suggest the associations of suicide with socio-economic determinants (unemployment rate, birth rate and life expectancy at birth). Moreover, our qualitative evaluation of the empirical results has also provided another meaningful argument to the verified determinants.